Improving health through addressing nutrition and sanitation in the Thar Desert, India - Prakash Tyagi (Elsevier, 2018)
Background: The Thar Desert of India is a severely drought-prone and impoverished region. As a result of water scarcity, communities live in deep-rooted poverty, which has a major impact on health status. Lack of nutritious foods leads to malnutrition and the scarcity of water also poses sanitation challenges. Nutrition and sanitation are therefore two critical health challenges in the region. GRAVIS, a non-governmental organisation, has launched an intervention known as Improving Health through addressing Nutrition and Sanitation (IHNS) in Thar. Methods: The programme has two main focuses. First, to address nutrition, a community-based nutrition curriculum has been designed to enhance knowledge on nutritional facts. The curriculum is used in schools for children and in the community for adults. Further, the concept of Household Horticulture Units has been developed whereby domestic waste water is used for growing fruits and vegetables. Second, on sanitation, low-cost, low-water-use toilets have been designed. Various toilet models have been studied to produce the optimum design for desert conditions. Bio-sand-water filters have been designed that provide rural people with potable water. A cadre of village health workers has been developed that constantly educates communities. In the past 5 years, GRAVIS has covered over 4000 people with these interventions with a holistic approach. GRAVIS conducts an annual review of the programme to understand outcomes. The annual review is done through a participatory approach in which communities are fully involved, and inputs are taken from concerned local government health authorities. GRAVIS and an external reviewer do a beneficiary survey with the help of a questionnaire and focus group discussions with key informants from the communities to understand the progress made and challenges encountered. The review report helps us analyse the outcomes and plan future interventions. In the annual review, we cover at least 20% of our beneficiaries. The selection is done on a random basis. The last annual review was done in January, 2017. Findings: About 60% of beneficiaries report significant improvement in their general health, as reported in a health study by GRAVIS in 2017, which included about 200 households and about 1400 individuals. In the project area, which included more than 250 school children, more than 90% of school children were fully aware of their nutritional requirements. According to outpatient records from the GRAVIS hospital in the area, the incidence of diarrhoeal disease has decreased by 20% in the past 2 years. The interventions are low cost, well accepted, and sustainable. Interpretation: Moving forward, GRAVIS envisions scaling up the IHNS model. It will be an effective approach to combat nutrition- and sanitation-related health issues, particularly in arid settings. GRAVIS foresees for itself a role as educator and provider of resources to help other organisations implement IHNS. We will explore resources and funding partnerships for replication and scale up. Funding: Government of Finland and People for Progress in India, USA.